Respiration‐Induced Weakening of Land Sink Contributed to the Largest CO 2 Increase in 2024 - Chaoya Dang; Zihua Shi; Josep Peñuelas; Philippe Ciais; Stephen Sitch; Jingfeng Xiao; Xing Li; Yanfeng Ding; Songhan Wang (Global Change Biology, 2026)
In 2024, the global annual growth rate of atmospheric CO 2 (CGR) surged to a record of 3.73 ppm year −1 —the highest since 1959—exceeding the 1.5°C climate threshold for the first time. However, the drivers behind this unprecedented rise remain poorly understood. Here, we employed a machine‐learning approach integrating satellite‐derived gross primary productivity (GPP) and climatic data to estimate the 2024 land sink (S LAND ) at approximately 2.21 ± 0.25 GtC year −1 , which had a striking decline of 1.01 GtC year −1 compared to the 2014–2023 average. The reduction in S LAND , most pronounced in tropical regions, contributed ~50% to the 2024 CGR increase—a larger impact than that of fossil fuel emissions or ocean sinks. Moreover, using partial least squares structural equation modelling, we further explained the underlying mechanism for the reduction of the S LAND in 2024, which was caused by hotter and drier conditions leading to a larger increase in respiration than photosynthesis. Our findings underscore the urgent need to investigate the mechanisms behind the declining carbon sink amid persistent global greening. These results challenge previous assumptions about the long‐term stability of the terrestrial carbon sink and highlight society's growing dependence on adaptive strategies to mitigate climate warming.